The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/biom10010033
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng Pharmacopuncture: Current Status of the Research and Future Challenges

Abstract: Despite the increasing use of ginseng pharmacopuncture in clinical practice, evidence of its physiological effects, safety, and clinical outcomes is insufficient. The purpose of this review is to summarize previous studies and suggest future challenges for the clinical use of ginseng pharmacopuncture. We systematically searched clinical and animal studies that applied ginseng pharmacopuncture and reviewed the manufacturing processes of ginseng pharmacopuncture solution, safety, physiological responses, and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 40 publications
(52 reference statements)
0
21
0
1
Order By: Relevance
“…A category of triterpene and saponin ginsenosides are divided into two forms: tetracyclic triterpenoids (four-ring dammarane type) and pentacyclic triterpenoids (five-ring oleanolic type) [ 4 ]. The dammarane type saponins are further categorized into protopanaxadiol (PPD) and protopanaxatriol (PPT) saponins [ 5 ]. The ginsenosides of PPD group constitute Compound K (CK), Rg3, Ra1, Ra3, Ra2, Rh2, Rb1, Rb3, Rb2, F2, Rc, and Rd, while PPT group constitutes of F1, Rg1, Rg2, Rf, Re, and Rh1 [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A category of triterpene and saponin ginsenosides are divided into two forms: tetracyclic triterpenoids (four-ring dammarane type) and pentacyclic triterpenoids (five-ring oleanolic type) [ 4 ]. The dammarane type saponins are further categorized into protopanaxadiol (PPD) and protopanaxatriol (PPT) saponins [ 5 ]. The ginsenosides of PPD group constitute Compound K (CK), Rg3, Ra1, Ra3, Ra2, Rh2, Rb1, Rb3, Rb2, F2, Rc, and Rd, while PPT group constitutes of F1, Rg1, Rg2, Rf, Re, and Rh1 [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical composition of ginseng can be mainly divided into two main types: saponin and non-saponin. Most ginseng components are non-saponin and include carbohydrates, nitrogen-containing compounds, fat soluble components, minerals, and vitamins [ 33 , 34 ]. Carbohydrates in ginseng include polysaccharides, oligosaccharides, sugar, fiber, and pectin, with the largest and active carbohydrates being polysaccharides, comprising 50–60% of ginseng components [ 33 , 35 ].…”
Section: Components Of Ginsengmentioning
confidence: 99%
“…Most ginseng components are non-saponin and include carbohydrates, nitrogen-containing compounds, fat soluble components, minerals, and vitamins [ 33 , 34 ]. Carbohydrates in ginseng include polysaccharides, oligosaccharides, sugar, fiber, and pectin, with the largest and active carbohydrates being polysaccharides, comprising 50–60% of ginseng components [ 33 , 35 ]. The next major components in ginseng are nitrogen-containing compounds—protein, peptides, amino acids, nucleic acids, and alkaloids [ 36 ], while fat soluble components consist of fatty acids, essential oils, phytosterol, organic acids, phenolics, and polyacetylenes [ 37 ].…”
Section: Components Of Ginsengmentioning
confidence: 99%
“…PG contains many effective ingredients, including panaxoside A, B, C, D, E, and F; monosaccharide; PG acid (a mixture of palmitic acid, stearic acid, and linoleic acid); vitamins (B1, B2, nicotinic acid, niacinamide, and pantothenic acid); amino acids; choline; enzymes (maltase, invertase, and esterase); spermine; and choleamine. 17,18 Previous studies have suggested that PG has many pharmacological effects, including anticancer, 19 antineuronal apoptosis, 20 antidiabetic, 21 anti-cognitive impairment, 22 antihypertensive, 23 and anti-fatigue 24 activities.…”
Section: Pharmacological Studies Of the Active Compounds Of Nine Chinmentioning
confidence: 99%